MODERATE EFFECT OF INSTITUTIONAL OWNERSHIP ON FINANCIAL DISTRESS, FREE CASH FLOW AND TAX PLANING ON REAL EARNING MANAGEMENT - Assa'adatul Khairiyahtussolihah; Wildan Aji Darussalam; Annida Karima Sovia (Jurnal Ekonomi, 2022)
The purpose of this study is to determine the Effect of Financial Distress, Free Cash Flow and Tax Planning on Real Earning Management with Institusioanl Ownership as a moderating variable. Sample collection was carried out using a purposive sampling method with total sample 187 companies during the 2014-2019 period. The analytical tool used is multiple linear regression. The results of this study indicate that Financial Distress has a significant positive effect on Real Earning Management. Whereas Free Cash Flow and Tax Planning have no significant positive effect on Real Earning Management. Good Corporate Governance which is proxied by Intitusional Ownership can reduced the influence of Financial Distress on Real Earning Management. Intitusional ownership is not able to reduced the influence between Free Cash Flow and Tax Planning on Real Earning Management.